2015
DOI: 10.1371/journal.pone.0134164
|View full text |Cite|
|
Sign up to set email alerts
|

Do Nobel Laureates Create Prize-Winning Networks? An Analysis of Collaborative Research in Physiology or Medicine

Abstract: Nobel Laureates in Physiology or Medicine who received the Prize between 1969 and 2011 are compared to a matched group of scientists to examine productivity, impact, coauthorship and international collaboration patterns embedded within research networks. After matching for research domain, h-index, and year of first of publication, we compare bibliometric statistics and network measures. We find that the Laureates produce fewer papers but with higher average citations. The Laureates also produce more sole-auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 23 publications
4
46
0
1
Order By: Relevance
“…In a similar study with Nobel Laureates and Non-Nobel Laureates, researchers found that although the laureates had a lower number of coauthors across their careers, they were as collaborative as non-laureates, and more likely to span a network to create a collaboration, positioning themselves for new discoveries 14 . The researchers posit that through their own visibility laureates can broker their network connections, and engage more frequently in activities that revel to them structural holes and opportunities for new knowledge development that keeps them on the forefront of scientific discovery 14 . Future research could include examination of productivity of networks and detailed examination of the specific partnerships within networks.…”
Section: Final Considerationsmentioning
confidence: 99%
“…In a similar study with Nobel Laureates and Non-Nobel Laureates, researchers found that although the laureates had a lower number of coauthors across their careers, they were as collaborative as non-laureates, and more likely to span a network to create a collaboration, positioning themselves for new discoveries 14 . The researchers posit that through their own visibility laureates can broker their network connections, and engage more frequently in activities that revel to them structural holes and opportunities for new knowledge development that keeps them on the forefront of scientific discovery 14 . Future research could include examination of productivity of networks and detailed examination of the specific partnerships within networks.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Further work needs to be done to establish to what extent efforts akin to the Nobel Prizes, say, promote riskier scientific strategies. I'm no expert on any of the sciences that get Nobels, nor on the prizes themselves, but it would be interesting to consider what effects such high-impact 'heroic' awards in fact have on scientific communities (see, for instance, Wagner et al 2015).…”
Section: The Epistemic Situation Of Existential Riskmentioning
confidence: 99%
“…What this scholar referred to as "unfocused" scholarship could also be seen as diverse and boundary-spanning. Recent work has suggested that top-performing researchers form coauthorship networks that tend to be well connected and structured for bridging structural holes (Wagner et al, 2015); in this light, this interdisciplinary researcher may share characteristics with some of the world's most impactful scientists. This scholar enjoyed seeing his story visualized in this way and wanted to feature the graph on his personal website.…”
Section: Stories From the Scholarsmentioning
confidence: 99%